Upaya Surat Kabar Harian Umum Haluan Padang Dalam Mempertahakan Eksistensi Di Era Media Online - Rahmatullah, Ikh'wan; Flowerina, Indria (CV. ITTC INDONESIA, 2024)
The rapid development of information and communication technology has caused a shift in information consumption patterns in society which has resulted in competition in the media industry, one of which is print media, where currently print media not only competes with other print media, but also competes with online media which is much interactive and interactive. efficient. Many newspapers have gone out of business because they failed to maintain their existence amidst the rapid growth of online media. This research aims to determine the efforts made by the Haluan Padang General Daily Newspaper in maintaining its existence in the online media era as one of the oldest conventional media in West Sumatra. This research is descriptive qualitative research which produces descriptive data in the form of writing or speech, as well as the behavior of people being observed. This method is applied to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. To describe this research using the media convergence theory put forward by Henry Jenkins (2006) in his book entitled